Perkembangan Saluran Pembuangan dan Normalisasi Sungai di Kota Cirebon Pada Masa Kolonial (1870-1938) - Mutawally, Anwar Firdaus; Zakaria, Mumuh Muhsin; Falah, Miftahul (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to explain the development of drainage channels and river normalization in Cirebon City during the Dutch colonial period (1870-1938). This research was motivated by the lack of research regarding drainage channels and river normalization in Cirebon City during the colonial period. The method used is the historical method which includes four stages of work, namely heuristics, criticism, interpretation and historiography. The research results show that before the 20th century, Cirebon did not have any government-managed sewers at all. Therefore, city residents build sewers independently or use the surrounding environment to dispose of sewage and household waste. Construction of drainage channels and river normalization in Cirebon began in 1885 and peaked from 1918 to 1934. The development project was divided into South Cirebon and North Cirebon. The presence of sewers gave rise to toilet facilities in Cirebon City and developments in waste management.